Penguatan Jiwa Kewirausahaan Melalui Praktik Pembuatan Logo Produk pada Aplikasi Canva di SMA Muhammadiyah Bontomarannu - Nurul Huda Yus’an; Mukarramah Syukur; Dwi Ayu Siti Hartinah H; Arif Rahman Hasdik (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2025)
Schools play a strategic role in fostering an understanding of entrepreneurship from an early age to equip students to face future challenges. Strengthening entrepreneurial concepts is necessary to build knowledge and an adaptive mindset relevant to the dynamics of the workplace and everyday life. This Community Service (PkM) activity, conducted at Muhammadiyah Bontomarannu High School, aimed to foster students' entrepreneurial spirit through practical logo creation using the Canva app, as an effort to foster a culture of innovation within the school environment. The program was implemented in the odd semester and included a method that included explaining basic entrepreneurial concepts through presentations, educational YouTube videos, explanations of digital business opportunities, and hands-on practice in product logo creation. Nineteen students from grades 10, 11, and 12 participated in this activity. The results showed that students were able to understand the concepts of creativity and innovation more concretely. They also developed critical thinking and creative problem-solving skills through the logo design process using digital applications on mobile devices. These findings reflect the developing adaptive, creative, and solution-oriented abilities of Muhammadiyah Bontomarannu High School students. Overall, this activity is an initial step in instilling an entrepreneurial mindset while strengthening a culture of innovation within the school environment and in daily life.